Selective collection in Brazil: a bibliometric analysis from 2000 to 2021 (Research, Society and Development, 2021)
The selective collection of recyclable materials is an important factor for environmental protection and economic and social development of recyclable material collectors. The research aims to present the state of the art of a selective collection of recyclable materials in Brazil. The approach is qualitative and refers to descriptive research from bibliometric techniques by the CAPES Journal database. The search with the term "Selective Collection" and "Brazil" in the title, abstract, keywords, resulted in a sample of 447 articles between 2000 and 2020. Show up the curve of the largest publications that occurred in 2015 as also the squares of publications are concentrated in the Southeast region of Brazil. The journal that was most published was the Environmental Monographs. The most cited keywords were public health, recycling, environmental education, in addition to the word Brazil.